Effectiviness of Using Artificial Intelligence Technology in Predicting Company Financial Performance in The Capital Market - Tandungan, Juan Edward; Mariani, Mariani; Prasasta, Zainal Dwi; Haeril, Andi; Normirawati, Normirawati (Phinisi Applied Accounting Journal, 2025)
This research examines the effectiveness of Artificial Intelligence (AI) technology in predicting the financial performance of companies in the capital market. Through a qualitative descriptive approach using literature study methods, this research analyzes various implementations of AI algorithms such as machine learning and deep learning in the context of financial analysis. Secondary data sources including scientific journals, articles, and relevant publications are reviewed to identify capabilities, limitations, and added value of AI technology compared to conventional analysis methods. The results show that AI technology has significant potential in improving the accuracy of financial performance predictions through its ability to process large-scale data and identify hidden patterns that are difficult to detect through manual analysis. However, effective implementation of AI technology still faces challenges such as data quality, algorithmic bias, and interpretability limitations. This research contributes to a comprehensive understanding of the role of AI technology in transforming capital market analysis and provides important implications for investors, financial analysts, and regulators in optimizing the use of AI for more measured investment decision-making.Keywords:, Artificial Intelligence, Financial Performance, Prediction, Capital Market, Penelitian ini mengkaji efektivitas teknologi Kecerdasan Buatan (AI) dalam memprediksi kinerja keuangan perusahaan di pasar modal. Melalui pendekatan deskriptif kualitatif dengan menggunakan metode studi pustaka, penelitian ini menganalisis berbagai implementasi algoritma AI seperti machine learning dan deep learning dalam konteks analisis keuangan. Sumber data sekunder meliputi jurnal ilmiah, artikel, dan publikasi relevan ditinjau untuk mengidentifikasi kemampuan, keterbatasan, dan nilai tambah teknologi AI dibandingkan dengan metode analisis konvensional. Hasil penelitian menunjukkan bahwa teknologi AI memiliki potensi yang signifikan dalam meningkatkan akurasi prediksi kinerja keuangan melalui kemampuannya dalam mengolah data berskala besar dan mengidentifikasi pola tersembunyi yang sulit dideteksi melalui analisis manual. Namun, implementasi teknologi AI yang efektif masih menghadapi tantangan seperti kualitas data, bias algoritmik, dan keterbatasan interpretabilitas. Penelitian ini berkontribusi pada pemahaman yang komprehensif tentang peran teknologi AI dalam mentransformasi analisis pasar modal dan memberikan implikasi penting bagi investor, analis keuangan, dan regulator dalam mengoptimalkan penggunaan AI untuk pengambilan keputusan investasi yang lebih terukur. Keywords :, Kecerdasan Buatan, Kinerja Keuangan, Prediksi, Pasar Modal,